2017
DOI: 10.3389/fevo.2017.00128
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Phytoplankton Biomolecule Availability for Secondary Production

Abstract: The growth and reproduction of animals is affected by their access to resources. In aquatic ecosystems, the availability of essential biomolecules for filter-feeding zooplankton depends greatly on phytoplankton. Here, we analyzed the biochemical composition, i.e., the fatty acid, sterol and amino acid profiles and concentrations as well as protein, carbon, nitrogen, and phosphorus content of 17 phytoplankton monocultures representing the seven most abundant phytoplankton classes in boreal and sub-arctic lakes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
128
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(135 citation statements)
references
References 56 publications
3
128
4
Order By: Relevance
“…Therefore, measuring only juvenile growth rates could have revealed greater differences among diet treatments, but it was unfortunately not possible in our study. Overall, the growth rates of Daphnia in our experiments (II and III) on diets with varying proportion and content of tPOM were lower than in previous studies, where Daphnia were fed solely with phytoplankton for similar time periods (Hiltunen et al., ; Peltomaa et al., ). The reproductive output of Daphnia was slightly enhanced when they were fed aged tPOM compared to fresh tPOM, but only when the proportion of tPOM in the diet was very high (≥95%).…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Therefore, measuring only juvenile growth rates could have revealed greater differences among diet treatments, but it was unfortunately not possible in our study. Overall, the growth rates of Daphnia in our experiments (II and III) on diets with varying proportion and content of tPOM were lower than in previous studies, where Daphnia were fed solely with phytoplankton for similar time periods (Hiltunen et al., ; Peltomaa et al., ). The reproductive output of Daphnia was slightly enhanced when they were fed aged tPOM compared to fresh tPOM, but only when the proportion of tPOM in the diet was very high (≥95%).…”
Section: Discussioncontrasting
confidence: 75%
“…However, the mean number of neonates and eggs produced by Daphnia was very low (<6 per individual), even in the treatments with 25% phytoplankton. Previous studies have found that Daphnia typically produce > 20 eggs and neonates in 14 days when solely fed phytoplankton (excluding cyanobacteria) (Brett et al., ; Hiltunen et al., ; Peltomaa et al., ). Although our hypothesis 2 was supported since Daphnia performance was slightly enhanced with aging of tPOM, our results indicate that even tPOM aged for a long time is a much inferior food source for Daphnia compared to algae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As bacteria contains equal EAAs to phytoplankton while tPOM is distinctly lacking in overall abundance of EAA, the EAA limitation of zooplankton in dystrophic lakes likely happens when zooplankton are forced to feed on terrestrial organic matter. These low nutritional quality periods can lead to decreased growth and reproduction of zooplankton due to the lack of both EAA and ω‐3 PUFA (Kleppel, Burkart, & Houchin, ; Peltomaa et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate quality diet for zooplankton includes all essential biomolecules, but in low amounts, whereas poor quality diet lacks some of the essential biomolecules. Daphnia can achieve high somatic growth with high or intermediate quality diet, whereas high reproduction rate requires high amounts of all essential biomolecules (Peltomaa et al., ). Generally, cryptophytes, synurophytes, and diatoms are high‐quality food for Daphnia , whereas green algae are intermediate quality due to the lack of EPA (Peltomaa et al., ).…”
Section: Introductionmentioning
confidence: 99%